Treatment of soybean seeds with molybdenum and inoculant: nitrate reductase activity and agronomic performance - Gewehr, Ewerton; Corrêa, Otávio de Oliveira; Suñé, Anna dos Santos; Duarte, Gabriel Bandeira; Amarante, Luciano do; Tunes, Lilian Vanussa Madruga de; Brandstetter Rodrigues, Daniele (Comunicata Scientiae, 2019)
The aim of this study was to analyze the effects of molybdenum and inoculant application via seed treatment in soybean, and their role in the nitrate reductase enzyme activity, agronomic traits and physiological quality of the produced seeds. The experiment was conducted at the Federal University of Pelotas (UFPel), Rio Grande do Sul state, Brazil. The treatments were shaped by five doses of molybdenum (zero; 16; 32; 48; 64 g.100kg-1 of seeds) combined with the presence and absence of liquid inoculant (Bradyrhizobium japonicum), at a dose of 200 mL per 100 kg of seeds. The evaluations of nitrate reductase activity, agronomic traits and physiological seed quality were performed in the present work. The measured agronomic traits were: plant height, number of pods per plant, number of seed per plant and thousand-seed weight. Standard germination test was executed to evaluate the produced seed viability. First germination counting, accelerated aging test, cold test, plantlet shoot and root length, plantlet shoot and root dry mass, and field seedling emergence were utilized to measure the seed vigour. Molybdenum, both in presence and absence of inoculant, positively influenced the enzymatic activity, for both vegetative and reproductive stages. The addition of inoculant and molybdenum provided increase in the vigour of the produced seeds. The enzyme activity was positively correlated with the agronomic traits and vigour tests. The addition of inoculant and molybdenum in the seed treatment provides a better expression of nitrate reductase activity and vigour of the produced seeds.